Usulan Perbaikan Kualitas Produk Pipa Api 5L PSL2 Menggunakan Metode Six Sigma - Nalhadi, Ahmad; Aida, Nur; Ramayanti, Gina (Universitas Serang Raya, 2018)
The production process of API 5L PSL2 pipes in Pipe Companies in 2017 happened to defect products at 7%. This defect is still above the standards set by the Company at 4%. The study aims to determine the value of sigma and provide recommendations for improvement with the six sigma method. Based on the results of the DMAI analysis, the amount of the pipe sigma level was 3.65 with the value of DPMO 14448. Types of defects identified in the process such as open welding defects, high lows, contact marking, scarring, and under dimension Proposed improvements were made by designing recommendations for improvements using 5W + 1H by checking the condition of the forming machine and changing bearing components before the bearing lifetime, performing preventive maintenance every week and adding coolant bursts to the cutting tool.